2017
DOI: 10.1016/j.rcot.2017.09.344
|View full text |Cite
|
Sign up to set email alerts
|

Open subpectoral biceps tenodesis in patients over 65 does not result in an increased rate of complications

Abstract: Background: Long head biceps tendon pathology is a common cause of anterior shoulder pain and is often associated with other shoulder conditions, such as rotator cuff tears and osteoarthritis. It is well accepted that older patients are at increased risk for major and minor peri-and postoperative complications. The purpose of this study is to investigate patients over 65 years old who underwent subpectoral biceps tenodesis and compare the complication rates of this group to those of patients younger than 65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The overall complication in the interference screw fixation with the tie over screw technique was 5.2% (21 of 408 patients) in five studies 10 29–32. The number of fixation complications in one study by Voss was not identified making the fixation complication 1.1% (33 of 94 patients)32 (tables 1 and 3).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The overall complication in the interference screw fixation with the tie over screw technique was 5.2% (21 of 408 patients) in five studies 10 29–32. The number of fixation complications in one study by Voss was not identified making the fixation complication 1.1% (33 of 94 patients)32 (tables 1 and 3).…”
Section: Resultsmentioning
confidence: 94%
“…Interference screw fixation with tie over screw technique had significant improvement of postoperative ASES Score in 4 studies of 4 studies that reported both preoperative and postoperative scores,29–32 CM score 1 of 1 study,32 VAS pain score 3 of 3 studies 29–31…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no other study has identified prognostic variables associated with biceps tenodesis complications or failures. The influence of age on the complication rate after biceps tenodesis was recently studied by Voss et al, 19 who found that patients older than 65 years did not have an increased risk of complications after biceps tenodesis. The present study supports this finding for both arthroscopic and open biceps tenodesis in older populations.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology of the long head of the biceps is a common source of anterior shoulder pain and is often associated with other intra-articular shoulder pathology. 23,25 Two established surgical treatment options are biceps tenotomy and tenodesis. These procedures can address a number of internal derangements associated with the long head of the biceps tendon, including tendinopathy and SLAP (superior labrum anterior to posterior) tears.…”
mentioning
confidence: 99%